Gamification and ICT in literacy training. An innovative didactic proposal in Secondary School - Martí Climent, Alicia; García Vidal, Pilar (Didáctica. Lengua y Literatura, 2021)
Gamification in literacy training may provide a serie of advantages in its didactic implementation so that it makes an impact in a meaningful learning in the classroom. Participants enrolled in teams, taking part in this work experience, have to achieve a challenge by solving a serie of mysteries or related tasks before the set time. In this way, students read, perform, dialog, write and create in order to achieve the aim and solve the situation. Through the digital resources and comprehension reading the mystery can be solved, taking always into account the collaborative work. An original final product can be produced to be shared and disseminated easily.
Keywords: Gamification in education; ICT; Literature; Educational innovations